ANALISIS KINERJA KOMISI PEMILIHAN UMUM PADA PILKADA 2018 DI SUMATERA UTARA - Arifin Sihombing; Sutarto Sutarto; Besti Rohana Simbolon; Fendrikus Laia (JURNAL GOVERNANCE OPINION, 2019)
As 2018 local election organizer, General Election Commissions (KPU) of North Sumatra plays an active role in succeeding of election activities and increases voter participation. This study aims at determining how the performance of The North Sumatera Provincial KPU in 2018. This research method is descriptive qualitative where data collected are in the form of words and images, not numbers as in quantitative research. This research was conducted in Medan at the Provincial KPU office and several agencies because the informants came from the party supporting both candidates for governor, Ombudsman, academic and KPU candidates. Based on the results of the study, the researchers conclude that, the North Sumatra Provincial KPU has served well and consistently in accordance with the tasks charged. From the eleven informants, eight have argued that the General Election Commission of North Sumatra Province already have a good category. One said the performance was classified as neutral, had done it but had not been significant in the quality difference from before. Two other informants said that it was not good because in some areas there was a re-election. General Election Commission of North Sumatra Province is not intervened by any party in carrying out their duties and in the dissemination of information such as socialization; it involves mass media so that the public knows all the stages. It has carried out its duties and functions in accordance with the provisions of the Election Law which have been designated as election organizers.